2011
DOI: 10.4013/nbc.2011.62.02
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the spatial distribution of the endemic and threatened palm shrub Syagrus glaucescens (Arecaceae)

Abstract: This study tests the use of accessible geoprocessing techniques to identify and describe the distribution of Syagrus glaucescens, a threatened palm shrub endemic to rupestrian fields (high-altitude grasslands) of the southern Espinhaço Range, in Minas Gerais, Brazil. A hundred and ninety five occurrence points and 24 absence points of S. glaucescens were recorded on a GPS device during field trips. Free databases of eight abiotic variables for the surveyed area were also used. Ninety-eight of the occurrence po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…In addition, understanding the reproductive cycles of plants is of fundamental importance for the conservation and management of native and endangered species. However, phenological studies on plants of the Pantanal biome are scarce, especially in endemic species, such as the carandá (Coelho & Machado, 2009;Conceição et al, 2007;Dutra et al, 2009;Miola et al, 2011).…”
Section: Introduction and Objectivesmentioning
confidence: 99%
“…In addition, understanding the reproductive cycles of plants is of fundamental importance for the conservation and management of native and endangered species. However, phenological studies on plants of the Pantanal biome are scarce, especially in endemic species, such as the carandá (Coelho & Machado, 2009;Conceição et al, 2007;Dutra et al, 2009;Miola et al, 2011).…”
Section: Introduction and Objectivesmentioning
confidence: 99%
“…In addition, understanding the reproductive cycles of plants is of fundamental importance for the conservation and management of native and endangered species. However, phenological studies on plants of the Pantanal biome are scarce, especially in endemic species, such as the carandá (DUTRA et al, 2009;MIOLA et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It was included in the list of threatened species of the International Union for Conservation of Nature and Natural Resources (Vulnerable category) as a result of its small distributional area and high destruction of its native habitat (Noblick 1998). Despite this fact, the few studies on S. glaucescens are restricted the phenology (Miola et al 2010;Belo et al 2013) and spatial distribution (Miola et al 2011). Miola et al (2010) also observed resistance and increased flowering after fire.…”
Section: Studied Speciesmentioning
confidence: 99%
“…Syagrus glaucescens is a small palm with distribution strongly associated with quartzite outcrops that occurs in the rupestrian grasslands from Serra do Cipó to Diamantina (Miola et al 2011). It was included in the list of threatened species of the International Union for Conservation of Nature and Natural Resources (Vulnerable category) as a result of its small distributional area and high destruction of its native habitat (Noblick 1998).…”
Section: Studied Speciesmentioning
confidence: 99%